Systemic chemotherapy before cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) in patients with high-grade mucinous carcinoma peritonei of appendiceal origin. Issue 9 (September 2019) - Munoz-Zuluaga, Carlos A.; King, Mary Caitlin; Ledakis, Panayotis; Gushchin, Vadim; Sittig, Michelle; Nieroda, Carol; Zambrano-Vera, Katherine; Sardi, Armando
Abstract: Background: The role of systemic chemotherapy (SC) before cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) in appendiceal high-grade mucinous carcinoma peritonei (HGMCP) is controversial. We analyzed the effect of SC prior to CRS/HIPEC in HGMCP. Methods: A prospective database of CRS/HIPEC procedures for HGMCP without signet ring cells and with signet ring cells (HGMCP-S) from 1998 to 2017 was reviewed. Exclusion criteria was prior surgery >5 regions or >2 regimens of prior SC. Perioperative variables were analyzed. Results: There were 140 HGMCP/HGMCP-S identified: 64 with prior SC (preSC) and 76 without (noSC). Groups were balanced for lymph node status, complete cytoreduction rate, disease burden, complications, and postoperative SC. PreSC had more HGMCP-S, moderately/poorly differentiated histology, and longer time-to-surgery (median: 6 vs 2 months, p < 0.001). Median overall survival (mOS) was 40 vs 86 and median progression-free survival (mPFS) was 19 vs 43 months for preSC vs noSC, respectively (p = 0.006 and p = 0.007). In HGMCP-S subanalysis, mOS was 25 vs 39 and mPFS 16 vs 29 months for preSC vs noSC, respectively (p = 0.188 and p = 0.063). In moderately/poorly differentiated histology subanalysis, mOS was 38 vs 56 and mPFS 18 vs 29 months in preSC vs noSC, respectively (p = 0.199 and 0.082). Prior SC was not linked to improved OS or PFS in non-signet ring HGMCP or well-differentiated histology subanalysis. Conclusion: Prior SC was not associated with less disease burden, better cytoreduction rates, or improved clinical outcomes in HGMCP, regardless of histopathologic subtype. Traditional SC agents may not be effective in HGMCP in the neoadjuvant setting. Abstract : The use of systemic chemotherapy (SC) before cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in advanced peritoneal carcinomatosis from appendiceal origin is not associated with less disease burden, better cytoreduction rates, or improved clinical outcomes. Traditional SC agents may not be effective in the neoadjuvant setting, thus other regimens are needed.